Sedimentology of the continental end‐Permian extinction event in the Sydney Basin, eastern Australia. Issue 1 (24th September 2020) - Fielding, Christopher R.; Frank, Tracy D.; Tevyaw, Allen P.; Savatic, Katarina; Vajda, Vivi; McLoughlin, Stephen; Mays, Chris; Nicoll, Robert S.; Bocking, Malcolm; Crowley, James L.
Abstract: Upper Permian to Lower Triassic coastal plain successions of the Sydney Basin in eastern Australia have been investigated in outcrop and continuous drillcores. The purpose of the investigation is to provide an assessment of palaeoenvironmental change at high southern palaeolatitudes in a continental margin context for the late Permian (Lopingian), across the end‐Permian Extinction interval, and into the Early Triassic. These basins were affected by explosive volcanic eruptions during the late Permian and, to a much lesser extent, during the Early Triassic, allowing high‐resolution age determination on the numerous tuff horizons. Palaeobotanical and radiogenic isotope data indicate that the end‐Permian Extinction occurs at the top of the uppermost coal bed, and the Permo‐Triassic boundary either within an immediately overlying mudrock succession or within a succeeding channel sandstone body, depending on locality due to lateral variation. Late Permian depositional environments were initially (during the Wuchiapingian) shallow marine and deltaic, but coastal plain fluvial environments with extensive coal‐forming mires became progressively established during the early late Permian, reflected in numerous preserved coal seams. The fluvial style of coastal plain channel deposits varies geographically. However, apart from the loss of peat‐forming mires, no significant long‐term change in depositional style (grain size, sediment‐body architecture, or sediment dispersal direction) was noted across the end‐Permian Extinction (pinpointed by turnover of the palaeoflora). There is no evidence for immediate aridification across the boundary despite a loss of coal from these successions. Rather, the end‐Permian Extinction marks the base of a long‐term, progressive trend towards better‐drained alluvial conditions into the Early Triassic. Indeed, the floral turnover was immediately followed by a flooding event in basinal depocentres, following which fluvial systems similar to those active prior to the end‐Permian Extinction were re‐established. The age of the floral extinction is constrained to 252.54 ± 0.08 to 252.10 ± 0.06 Ma by a suite of new Chemical Abrasion Isotope Dilution Thermal Ionization Mass Spectrometry U‐Pb ages on zircon grains. Another new age indicates that the return to fluvial sedimentation similar to that before the end‐Permian Extinction occurred in the basal Triassic (prior to 251.51 ± 0.14 Ma). The character of the surface separating coal‐bearing pre‐end‐Permian Extinction from coal‐barren post‐end‐Permian Extinction strata varies across the basins. In basin‐central locations, the contact varies from disconformable, where a fluvial channel body has cut down to the level of the top coal, to conformable where the top coal is overlain by mudrocks and interbedded sandstone–siltstone facies. In basin‐marginal locations, however, the contact is a pronounced erosional disconformity with coarse‐grained alluvial facies overlying older Permian rocks. There is no evidence that the contact is everywhere a disconformity or unconformity.